2013
DOI: 10.1038/nbt.2614
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of siRNA delivery by lipid nanoparticles is limited by endocytic recycling

Abstract: Despite substantial efforts to understand the interactions between nanoparticles and cells, the cellular processes that determine the efficiency of intracellular drug delivery remain largely unclear. Here we examined cellular uptake of siRNA delivered in lipid nanoparticles (LNPs) using cellular trafficking probes in combination with automated high-throughput confocal microscopy as well as defined perturbations of cellular pathways paired with systems biology approaches to uncover protein-protein and protein-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
701
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 717 publications
(724 citation statements)
references
References 41 publications
17
701
5
1
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Independent assays of endosomal escape. Although endosomal escape is widely considered to be the major bottleneck of cationic protein delivery 34 , few assays quantify the ability of proteins to escape endosomes on a single-cell basis. To quantify cytosolic delivery of supercharged proteins in individual cells, we applied a glucocorticoid receptor (GR) translocationassay 35 described by Schepartz and colleagues 9,36 .…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Independent assays of endosomal escape. Although endosomal escape is widely considered to be the major bottleneck of cationic protein delivery 34 , few assays quantify the ability of proteins to escape endosomes on a single-cell basis. To quantify cytosolic delivery of supercharged proteins in individual cells, we applied a glucocorticoid receptor (GR) translocationassay 35 described by Schepartz and colleagues 9,36 .…”
Section: Resultsmentioning
confidence: 99%
“…Second, after injection, these conventional cationic vectors bind to serum protein and thus are rapidly removed from the blood, with a circulation time less than 10 min,10 thus preventing localization to the desired tissues. Additionally, these vector/gene complexes tend to accumulate in lysosomes followed by internalization, and subsequently the obtained gene escapes from lysosomes by taking advantage of the “proton sponge effect” into the cytosol of target cells, where they associate with the target gene to exert their silencing function 11. Unfortunately, the escape efficiency of genes from lysosomes into the cytosol is extremely low at only 1–2%, and it only occurs in a short limited time‐period when the vectors are located in a specific compartment that shares both early and late endosomal characteristics 12.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the HCA study of the uptake of lipid NPs outlined above [81], siRNAs were used to deplete cells of fundamental endocytic machinery, and showed that lipid NPs primarily endocytose by either clathrin-mediation or macropinocytosis. The parallel study using a limited number of siRNAs also found that macropinocytosis (as judged by depletion of Cdc42 and Rac1) was important for the internalization of this particle type [82]. Thus, HCA, in combination with systematic RNAi, is likely to be a successful strategy to define more clearly at the molecular level the internalization mechanisms and intracellular trafficking pathways used by NPs.…”
Section: Hca: Detailed Mechanisms Of Np Internalization and Intracellmentioning
confidence: 91%
“…Escape of the siRNA from NPs was unexpectedly determined to be very low (1-2%), but the real impact lay in the harnessing of the instrumentation together with appropriate sample preparation to enable systematic study of the intracellular distribution of NPs. Others used high-throughout confocal microscopy to study the uptake and intracellular trafficking of siRNA-loaded lipid NPs, which were manufactured using microfluidics and included a cationic lipid (C12-200) [82]. The antiGFP siRNA-loaded NPs were used to transfect HeLa-GFP-expressing cells and several small molecule inhibitors were used that alter cell signaling and intracellular trafficking and that either inhibit or induce autophagy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%